2006
DOI: 10.1111/j.1365-294x.2005.02761.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and population genetics of the maize stalk borer Busseola fusca (Lepidoptera, Noctuidae) in sub‐Saharan Africa

Abstract: The population genetics and phylogeography of African phytophagous insects have received little attention. Some, such as the maize stalk borer Busseola fusca, display significant geographic differences in ecological preferences that may be congruent with patterns of molecular variation. To test this, we collected 307 individuals of this species from maize and cultivated sorghum at 52 localities in West, Central and East Africa during the growing season. For all collected individuals, we sequenced a fragment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
103
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 59 publications
14
103
0
1
Order By: Relevance
“…Th e molecular marker used is a fragment of the gene coding for the cytochrome b for which approximately 1000 bp were amplifi ed by PCR. Th e same primers and PCR protocol as described by Sezonlin et al (2006) were used for all samples. Amplifi ed PCR products were purifi ed with the Quick protocol (Promega Wizard SV Gel and PCR Clean-Up System) and directly sequenced on an automated sequencer ABI prism 377 using the amplifi cation primers in both directions.…”
Section: Molecular Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Th e molecular marker used is a fragment of the gene coding for the cytochrome b for which approximately 1000 bp were amplifi ed by PCR. Th e same primers and PCR protocol as described by Sezonlin et al (2006) were used for all samples. Amplifi ed PCR products were purifi ed with the Quick protocol (Promega Wizard SV Gel and PCR Clean-Up System) and directly sequenced on an automated sequencer ABI prism 377 using the amplifi cation primers in both directions.…”
Section: Molecular Analysismentioning
confidence: 99%
“…It is more adapted to lowland in West Africa than in East and Southern Africa (Kfi r et al 2002). Previous study on the genetic structure of B. fusca shows that this ecological preference is associated with major diff erences in partial DNA sequence of the cytochrome b mitochondrial gene (Sezonlin et al 2006). According to that study, B. fusca populations are diff erentiated into three major clades of mitochondrial haplotypes, one located in West African region (W), one restricted to East Africa (KI) and one found in Central and East Africa (KII).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To a first approximation, the whole population seems close to panmixia at coarse scales (700 km × 400 km). It has been suggested that B. fusca could be characterised by limited dispersal capacities (Sezonlin et al, 2006). However, consistent with Dupas et al (2014), our study did not reveal strong barriers to gene flow.…”
Section: Gene Flow and Resistance Spreadmentioning
confidence: 29%